Die Kinder- und Jugendzeichnungen der Brüder Grimm und ihrer Familie | The Children's and Youth Drawings of the Brothers Grimm and Family "Ein Fenster in die Vergangenheit" | "A Window into the Past" - Ströter-Bender, Jutta; Eikermann, Larissa; Völker, Susanne (KONTEXT Kunst - Vermittlung - Kulturelle Bildung, 2023)
It is hardly known that the brothers Jacob Grimm (1785-1883) and Wilhelm Grimm (1786-1859) drew intensively from their earliest childhood. This publication is devoted to their hitherto unexplored childhood and youth drawings as well as those of their siblings Carl, Charlotte, Ludwig Emil Grimm and their descendants. These are sketchbooks, drawing sheets and small watercolours, among which are also extraordinary studies of nature. Individual studies make these hitherto scarcely accessible documents of bourgeois children's and youth culture from the first half of the 19th century accessible in their contexts and at the same time open up the archival holdings of the Grimm Collection of the City of Kassel. With contributions by Kunibert Berin